Puppetry and acting: a reflection (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
This article is reflection on the actor puppeteer's performance: the act of performing and the methods and processes an actor-puppeteer must develop when manipulating in full-view of an audience.Keywords: Performance. Puppet. Techniques. Artistic approaches.